Beijing 2022 between urban renovation and Olympic sporting legacy: the case of Shougang - From space for event to space for health and leisure - Deng, H.; Mancini, M.; Zhang, L.; Bonino, M. (Movement & Sport Sciences - Science & Motricité, 2020)
Among urban redevelopment projects, the regeneration of industrial brownfields has become an important issue in North America, Europe and, more recently, China. At the same time, the influence of short-term mega events, such as the Olympic Games, on host cities transformations has been growing throughout the decades. Thus, planning and integrating long-term brownfields regeneration with the Olympic legacy provide numerous potentials. This paper presents a theoretical study of the Olympic event as catalyst of urban transformations and, specifically, of brownfields redevelopment. The early bidding phase should become the starting point to embed the Olympic tangible and intangible legacies into long-term objectives of urban renewal and sport and health enhancement. Shougang District, future location of the Big Air venue of Beijing Winter Olympic Games 2022, with its significant industrial heritage, is introduced as case study to present the on-going practice of architectural design, plan and management. The comprehensive development of a long-term Olympic legacy is developed along with the attention to urban renovation and social progress.